Religious pluralism in contemporary Malaysia : Muslim and Christian perspectives - Marina Munira Abdul Malik (International Institute of Islamic Civilisation and Malay World (ISTAC), International Islamic University Malaysia, 2018)
Religious diversity in Malaysia has led to the development of what social scientists refer to as “religious pluralism.” Comprising of major religions of the world such as Islam, Christianity, Buddhism, Hinduism, Taoism, Sikhism and “others,” it has recently become a challenge for Malaysia to manage religious diversity and maintain social harmony. Different interpretations of religious pluralism among scholars have resulted in misunderstanding of the concept, particularly among members of Muslim and Christian communities in the country. The discourse of “religious pluralism” started when some prominent Muslim scholars warned that Muslims in Malaysia are threatened by liberalism and religious pluralism, which can impinge into the faith of Muslims. The findings assert that different interpretations of religious pluralism among scholars have resulted in misunderstanding of the concept, particularly among members of Muslim and Christian communities in the country. The reactions from both Muslims and Christians have been coloured with religio-political voices. The main objective of this dissertation is to examine the current debate on religious pluralism in contemporary Malaysia. In doing so, the dissertation has conducted in-depth interviews with ten religious Christian and Muslim figures. It aims to present various academic interpretations of the term “religious pluralism” by leading Christian and Muslim figures to explore the contemporary religious experience in Malaysia. Questions have been asked to both religious groups in order to investigate their opinions and responses of the discourse of religious pluralism in Malaysia. The findings of the dissertation indicate that both terminologies of “religious pluralism” and “religious plurality” have been used interchangeably to connote the pluralistic identity of Malaysia. However, the term “religious pluralism” has been clearly identified with Hick and pluralist scholars and thus philosophically contested. Through the narratives of religious representatives it is found that religion contributes significantly to the development of Malaysian pluralistic society. The study also proposes a number of recommendations on how these religious groups can help nurture the essential values of unity (wuḥdah) in living with diversity.